Generating Cinema Knowledge - Engin Ayça (Filmvisio)
The essay discusses the necessity of generating original knowledge of the cinema both theoretically and practically. Cinema, which emerged within the capitalist system in Europe and the United States of America at the end of the 19th century, evolved within the framework of the historical and cultural heritage of Western nations. Consequently, cinema was shaped in accordance with the commercial and ideological objectives of Western countries and disseminated globally. The essay discusses the potential and possible consequences of transcending the conventions of this cinematic system, particularly within Turkish cinema.